Writing of the history and sexuality: Cassandra rios, absence and invisibility - Mantovani, Flavia [UNESP] (Universidade Federal da Fronteira Sul, 2021)
Rethinking the writing of the History is a task that has been occupying a considerable place in the production of historians, especially, throughout the 20th century. Considering other subjects, objects and views, the historiograph-ical field opens up to new problems. This text intends to present possibilities of writing of His-Tory in the interface with sexuality based on the literary production of Cassandra Rios (1932 2002), a writer known as the most forbidden in Brazil, it was concluded by the thirty books ve-Toed by censorship, also, in the military dicta-Torship. From some questions raised by the field of the History of Women, a possibility of writ-ing of History from the perspective of lesbian women is presented, considering the theme ap-proached by Rios in the most part of her writing, focused on stories of desire among women. In the end, perspectives are pointed out in Cassan-dra Rios to make visible these such subjects, generally absent in the historiography, and the potential of her literary production as a relevant source in the (re)writing of subjects history with dissident sexualities.
Escrita da Historia e sexualidade: Cassandra Rios, ausencia e invisibilidade
Keywords: Cassandra Rios; History writing; Lesbian literature; Literature and censorship; Sexuality and policy